Acupuncture in patients with trigeminal neuralgia–an exploratory mixed methods trial - Cedric von Angern; Nicolas Volz; Lars Neeb; Barbara Stöckigt; Petra Bäumler; Ina Koubeck; Stephanie Roll; Stefan N. Willich; Benno Brinkhaus; Joanna Dietzel (Frontiers in Medicine, 2026)
Background Trigeminal neuralgia (TN) is a chronic pain condition with limited treatment options. Acupuncture has been suggested as a complementary therapy; however, the current scientific evidence is limited. Study aim was to explore feasibility, effects and patient experience of acupuncture for TN in a routine care setting. Methods Randomized, open-label, exploratory, multicenter trial with mixed-methods. Patients with TN were randomized to acupuncture plus routine care or to routine care alone. Ten acupuncture sessions were administrated over 8 weeks. The control group received delayed acupuncture using the same protocol after week 12. All patients were followed for 52 weeks. Outcomes were assessed at weeks 8, 12, 20, and 52 including number and intensity of TN pain attacks, Barrow neurological institute Pain Intensity Score, Penn Facial pain, Quality of Life, hospital anxiety and depression, patient global impression of change (PGIC). A qualitative sub-study included six semi-structured patient interviews after completion of treatment, analyzed using content analysis. Results Twenty patients (mean age 63.4 years (SD: 15.1; range: 34–85) were included. Both groups showed a reduction in daily attack frequency, not meeting clinical relevance and with no relevant difference between groups (acupuncture: 4.4 (95% CI 1.4, 7.4) control: 4.3 (1.4, 7.1) in week 8), nor was there a relevant difference in daily pain attack intensity between groups (in week 8 mean NRS 3.3 (2.1, 4.5) vs. 3.8 (2.7, 4.9). There was no relevant difference between groups in the BNI or Penn-FPS-R nor the SF-12. Still the acupuncture group experienced greater subjective improvement in the PGIC. Qualitative findings supported the patient’s global impression, with patients describing acupuncture as preventive, calming, and emotionally supportive. The intervention was well accepted, with no serious adverse effects and minor adverse effects such as small hematomas at needling site. Conclusion This exploratory mixed-methods trial identified methodological pitfalls relevant to future TN research, including challenges in collecting reliable patient-reported outcomes and accurately documenting paroxysmal pain attacks. Future trials should simplify outcome assessment and reduce participant burden. An acupuncture series was shown to be a feasible, safe, and well-accepted intervention in TN, supporting its further evaluation in adequately powered RCTs. Clinical trial registration https://www.drks.de/drks_web/navigate.do?navigationId=trial.HTML&TRIAL_ID=DRKS00018776 , identifier DRKS00018776.